HAK KONSTITUSIONAL ATAS AIR PASCA DIHAPUSNYA UNDANG UNDANG NOMOR 7 TAHUN 2004 TENTANG SUMBER DAYA AIR OLEH MAHKAMAH KONSTITUSI - Nova Yarsina (Ensiklopedia Social Review, 2021)
The purpose of this study is to examine human rights over water after the abolition of Law Number 7 of 2004 concerning Water Resources by the Constitutional Court. The research method used is normative juridical. Later there was an opinion that if the state was unable to guarantee the fulfillment of human rights over water, then the water supply was carried out by a third party. The state must regulate the appropriateness of control over water sources, affordability of prices, guarantees for water health. For the realization of these things, a system of regulation must be made. An independent regulatory body can also be formed, public participation, and sanctions against violations. In essence, every regulation issued by the local government related to water use actually makes water as "Economic goods". Commercialization and privatization of water services is not an illegal thing as long as it can improve clean water services so that public access to water also increases. Local governments should be able to understand that commercialization of water resources by setting drinking water tariffs that exceed the capacity and reasonableness of the community actually results in reduced community access to water resources, especially clean water and drinking water. The poor and marginalized are the most vulnerable groups to the failure to fulfill the right to water by the State. To see the extent to which the fulfillment of the right to water by the state apart from the perspective of the executive authority, it is necessary to look at court decisions that can reflect the fulfillment of the right to water especially after the abolition of Law Number 7 of 2004 concerning Water Resources by the Constitutional Court and return to Law Number 11 of 1974 concerning Irrigation.